2009
DOI: 10.1590/s0100-204x2009000500005
|View full text |Cite
|
Sign up to set email alerts
|

Manejo do dossel vegetativo da videira e seu efeito na composição do vinho Merlot

Abstract: Resumo -O objetivo deste trabalho foi avaliar o efeito de modalidades de poda verde da videira (Vitis vinifera L.) na composição do vinho Merlot. Um experimento foi conduzido de 1993/1994 a 1996/1997, em Bento Gonçalves, RS, com uma testemunha e 11 modalidades de poda verde em vinhedo conduzido em latada. A análise de componentes principais mostrou que o efeito da poda verde variou conforme o ano. Considerando a média dos quatro anos avaliados, os três principais componentes foram responsáveis por 72% da varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 15 publications
1
2
0
2
Order By: Relevance
“…However, Merlot wine group was higher (p< 0.05) in total polyphenols index (19.5%), A 520 (46.7%), and color intensity (32.1%). In general, the data of the present study are similar to those already recorded in previous studies conducted in the same region on Merlot (Miele et al, 2009b) and Cabernet Sauvignon (Miele & Rizzon, 2019) wines. Polyphenols are very complex, important compounds for red wines, with anthocyanins and tannins the main substances in this group that could influence the characteristics and quality of the wine.…”
Section: Classical Variablessupporting
confidence: 92%
“…However, Merlot wine group was higher (p< 0.05) in total polyphenols index (19.5%), A 520 (46.7%), and color intensity (32.1%). In general, the data of the present study are similar to those already recorded in previous studies conducted in the same region on Merlot (Miele et al, 2009b) and Cabernet Sauvignon (Miele & Rizzon, 2019) wines. Polyphenols are very complex, important compounds for red wines, with anthocyanins and tannins the main substances in this group that could influence the characteristics and quality of the wine.…”
Section: Classical Variablessupporting
confidence: 92%
“…De fato, trabalho anterior realizado nesse mesmo vinhedo mostrou que a desbrota + desponta + desfolha realizada no início da floração, eliminandose as folhas abaixo dos cachos, proporcionou maior síntese e acúmulo de açúcar na uva, o que é expresso pelo ºBrix e pela densidade, e menor de acidez, expressa pelas concentrações dos ácidos tartárico e málico, pH e acidez titulável do mosto da uva Merlot (MANDELLI et al, 2008). Com relação ao vinho, eles se caracterizaram por maior intensidade de cor, absorbâncias a 520 nm e 280 nm, antocianinas, taninos, álcool, 3-metil-1-butano/1-propanol, álcool em peso/extrato seco reduzido, fósforo e cinzas (MIELE et al, 2009).…”
Section: Resultsunclassified
“…The acidity found in berries of vines is a result of the organic acids present in their composition and physicalchemical changes occurring in their maturation process, due to the degradation of the acids during the process of fruit respiration. In the case of grapes, acidity is also affected by the fermentative effect of certain yeasts, which may produce organic acids, in addition to the dissolution of minerals and acids released from their skin and pulp (Miele et al, 2009). It can be observed in this study that the application of defoliation is efficient only when the vines are cultivated under cover, in which case the application of 30% and 40% defoliation allows a rise in pH by up to 3.05, if the must is used for winemaking purposes.…”
Section: Resultsmentioning
confidence: 99%
“…Another practice that can be used to minimize the incidence of downy mildew is defoliation, with the aim of favoring aeration in the region of the inflorescences and bunches, thereby providing better conditions for maturation (Miele et al, 2009). Souza et al (2012) found that the presence of 5, 10 and 15 leaves in the production branch provided a longer berry volume and did not interfere in the production of the Superior Seedless cultivar.…”
Section: Introductionmentioning
confidence: 99%